2022
DOI: 10.3201/eid2808.212530
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Threat of G4 Genotype Eurasian Avian-Like Swine Influenza A(H1N1) Viruses, China, 2020

Abstract: P igs have long been considered a crucial genetic mixing vessel for influenza A viruses (IAVs) of different hosts (1) because of the dual expression of human (SAα-2,6Gal) and avian (SAα-2,3Gal) viral receptors on their respiratory epithelium. Swine IAVs such as H1N1 and H3N2 subtypes sporadically infect humans and are prone to cause bidirectional interspecies transmission at the swine-human interface (2-5). So far, Eurasian avian-like (EA) H1N1 has dominated prevalence in pig herds in China and caused >10 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…While EA swine H1N1 viruses have been circulating in Eurasian countries, G4 EA H1N1 viruses have emerged in China and have been predominant since 2016 [26]. G4 EA H1N1 viruses have severe pathogenicity, enhanced replication, and transmission ability in vivo and can be transmitted from pigs to humans [6,14,25].…”
Section: Discussionmentioning
confidence: 99%
“…While EA swine H1N1 viruses have been circulating in Eurasian countries, G4 EA H1N1 viruses have emerged in China and have been predominant since 2016 [26]. G4 EA H1N1 viruses have severe pathogenicity, enhanced replication, and transmission ability in vivo and can be transmitted from pigs to humans [6,14,25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise concerns about the new pandemic virus, as G4 possesses all the features crucial for human adaptation [43]. Gu et al (2022) observed high homology between two G4 swine isolates and contemporaneous humanorigin EA H1N1 [58]. Moreover, these strains could effectively replicate in mice lungs without previous adaptation, and one bound preferentially to human-like receptors.…”
Section: Pandemic Potentialmentioning
confidence: 99%
“…Moreover, these strains could effectively replicate in mice lungs without previous adaptation, and one bound preferentially to human-like receptors. Given the above research and the first confirmed human case of G4 infection, a possible threat to the public health of the G4 virus should not be ignored [58].…”
Section: Pandemic Potentialmentioning
confidence: 99%
“…AlphaFold-pairs was validated using two well-defined systems: the 12-subunit enzyme RNA polymerase II (Pol II), and the interaction of the SARS-CoV-2 Spike glycoprotein with human cell surface receptors. Using the AlphaFold-pairs method, we also successfully elucidated the interactions among viral proteins that comprise the reassortant Eurasian avian-like (EA) H1N1 swine G4 genotype Influenza A virus (IAV) variant, a zoonotic respiratory pathogen considered to pose a significant pandemic risk by the CDC and the WHO [8]. In addition, we also identified host interactors that associate with the G4 proteins.…”
Section: Introductionmentioning
confidence: 99%